"Crucial? Helpful? Practically Nil?" Reality and Perception of Britain's Contribution to the Development of Nuclear Weapons during the Second World War. Issue 1 (2nd January 2022) - Lee, Sabine
ABSTRACT: When, in March 1940, two Jewish emigré physicists, Otto Frisch and Rudolf Peierls, composed a memorandum on the technical feasibility of an atomic weapon, few would have envisaged the significance of this six-page document. The technical blueprint for an atomic weapon, at the time assumed to be well beyond the realm of the possible, was to have a significant impact on the Anglo-American nuclear relationship, as it enabled British and American scientists to discuss at eye-level, the direction of nuclear weapons development, as it moved from theory to implementation. Significantly, Peierls and Frisch calculated the critical mass uranium and concluded that the amount of U235 required for a bomb was in the region of kilos rather than tons, as previously thought. The document amplified the British voice in the Anglo-American discussions about the development of nuclear weapons which eventually led to the Manhattan Project, the US-led development of the bombs that would be dropped on Hiroshima and Nagasaki to end the war in the Pacific. Yet, the official history of the Manhattan Project claimed that the British contribution to the successful development of the weapon was 'in no sense vital' and the 'technical and engineering contribution … practically nil'. This paper discusses Britain's co-operation and competition in the Anglo-American nuclear relationship in the light of scientific collaboration and rivalry during the Second World War.